1997
DOI: 10.1104/pp.115.2.683
|View full text |Cite
|
Sign up to set email alerts
|

A Secreted Factor Inducs Cell Expansion and Formation of Metaxylem-Like Tracheary Elements in Xylogenic Suspension Cultures of Zinnia

Abstract: Conditioned medium from mesophyll cell-suspension cultures of Zinnia eregans 1. has striking effects on cell expansion and tracheary element differentiation when applied to cultures of freshly isolated mesophyll cells. These effects include (a) induction of early cell expansion, (b) delay in differentiation by 48 h or more, (c) reduction in the synchrony of differentiation, and (d) early formation of very large, metaxylem-like tracheary elements. Like reduced osmotic potential and buffering at pH 5.5, conditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 34 publications
0
15
0
Order By: Relevance
“…As an alternative, the spent medium of plant cell-suspension cultures can be collected in large volumes, facilitating the analysis of extraprotoplasmic oligosaccharides present at low concentration. Plant cell cultures have been shown to accumulate in the culture medium biologically relevant concentrations of certain oligosaccharins, including those derived from xyloglucans (Fry 1986), pectins (Tani et al 1992), Nlinked glycoproteins (Priem et al 1990;Priem and Gross 1992) and unidenti®ed sources (SchroÈ der and Knoop 1995; Roberts et al 1997). We are investigating the secretion of oligosaccharins by cultured Rosa cells (GarcõÂ a-Romera and Fry 1995Fry , 1997, and recently discovered in this source a novel trisaccharide, a-Dmannopyranosyl-(1 ® 4)-a-D-glucuronopyranosyl-(1 ® 2)-myo-inositol (MGI) (Smith et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…As an alternative, the spent medium of plant cell-suspension cultures can be collected in large volumes, facilitating the analysis of extraprotoplasmic oligosaccharides present at low concentration. Plant cell cultures have been shown to accumulate in the culture medium biologically relevant concentrations of certain oligosaccharins, including those derived from xyloglucans (Fry 1986), pectins (Tani et al 1992), Nlinked glycoproteins (Priem et al 1990;Priem and Gross 1992) and unidenti®ed sources (SchroÈ der and Knoop 1995; Roberts et al 1997). We are investigating the secretion of oligosaccharins by cultured Rosa cells (GarcõÂ a-Romera and Fry 1995Fry , 1997, and recently discovered in this source a novel trisaccharide, a-Dmannopyranosyl-(1 ® 4)-a-D-glucuronopyranosyl-(1 ® 2)-myo-inositol (MGI) (Smith et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these hormones, several factors have been shown to be involved in intercellular interactions during TE differentiation. An oligosaccharide-like secreted factor in Zinnia conditioned medium appeared to play an important role in cell expansion and metaxylem-like TE differentiation (Roberts et al 1997). Phytosulfokine-a secreted into Zinnia conditioned medium was suggested to be a factor responsible for TE differentiation (Matsubayashi et al 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Figure 4C revealed that MX differentiation may occur without an increase in cell volume, whereas mesophyll cells that undergo cell expansion may differentiate into PX. Thus, cell expansion and MX differentiation are not always intimately linked as previously described (Roberts et al, 1997;Pesquet et al, 2005).…”
Section: Ggmos Modify the Relative Proportion Of Px-and Mx-like Tesmentioning
confidence: 76%
“…These results suggest that mannans may be naturally occurring signaling molecules involved in TE differentiation. Moreover, an expansion-inducing factor, originally described as a secreted oligosaccharide, has been partially characterized from conditioned culture medium from 6-d-old zinnia cultures (Roberts et al, 1997). When expansion-inducing factor was added to fresh cultures, early production of MX was observed, providing further evidence that oligosaccharide signaling occurs in xylogenic zinnia cultures.…”
mentioning
confidence: 98%
See 1 more Smart Citation